The spectrum of cytokeratins expressed in the adult human cornea, limbus and perilimbal conjunctiva - Merjava, Stanislava; Neuwirth, Aleš; Tanzerová, Michaela; Jirsová, Kateřina (Histology and histopathology, 2011)
The aim of this study was to detect a spectrum of cytokeratins (CK) present in the adult human cornea, limbus and perilimbal conjunctiva. Cryosections from seven corneo-scleral discs were fixed, and indirect immunofluorescent staining was performed using antibodies directed against CK1-CK10 and CK13-CK20. The percentage of positive cells was calculated in the epithelium of the cornea, limbus and perilimbal conjunctiva. Quantitative real time RT-PCR (qRT-PCR) was used to detect CK6 and CK18 expression in the corneal and conjunctival epithelium. The most intense staining present throughout the cornea was observed for CK3, CK5 and CK14; CK19 was found at the corneal periphery only. CK4 and CK10/13 revealed mild to moderate positivity mostly in the superficial layers of the cornea. The suprabasal cell layers of all examined areas showed a strong positivity for CK16. A heterogeneous staining pattern with a centrifugal decrease in the signal was observed for CK8 and CK18. CK5/6, CK14 and CK19 were present in the limbus, where a positive signal for CK3 was observed in the suprabasal and superficial cells only. In contrast to the cornea, CK15 appeared in the basal and suprabasal layers of the limbus. The perilimbal conjunctiva showed strong immunostaining for CK10/13, CK14 and CK19. A moderate signal for CK7 was detected in the superficial layers of the conjunctiva. qRT-PCR confirmed CK6 and CK18 expression in the corneal and conjunctival epithelium. The detailed characterization of the corneal, limbal and perilimbal conjunctival epithelium under normal circumstances may be useful for characterizing the changes occurring under pathological conditions.
Keywords: fluorescenční protilátková technika nepřímá; skléra; Male; Conjunctiva; rohovka; fluorescenční mikroskopie; Epithelium, Corneal; Adult; konjunktiva; Aged; dospělí; glyceraldehyd-3-fosfátdehydrogenasy; imunohistochemie; senioři; mužské pohlaví; Fluorescent Antibody Technique, Indirect; polymerázová řetězová reakce s reverzní transkripcí; Keratins; Limbus Corneae; Sclera; lidé; Glyceraldehyde-3-Phosphate Dehydrogenases; RNA; ženské pohlaví; Immunohistochemistry; Microscopy, Fluorescence; Humans; Reverse Transcriptase Polymerase Chain Reaction; keratiny; Female; lidé středního věku; limbus corneae; Cornea; Middle Aged; rohovkový epitel